2010
DOI: 10.1002/bies.200900187
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C content in plants is modified by insects and influences susceptibility to herbivory

Abstract: Analysis of a diverse cross-sample of plant-insect interactions suggests that the abundance of vitamin C (L-ascorbic acid, ascorbate or AsA) in plants influences their susceptibility to insect feeding. These effects may be mediated by AsAs roles as an essential dietary nutrient, as an antioxidant in the insect midgut, or as a substrate for plant-derived ascorbate oxidase, which can lead to generation of toxic reactive oxygen species. Ascorbate can also influence the efficacy of plant defenses such as myrosinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 94 publications
1
33
0
Order By: Relevance
“…Ascorbate has multiple functions in animals and plants, including acting as an antioxidant, serving as a cofactor for various enzymes, and participating in cell signalling (Corti et al, 2010; Foyer and Noctor, 2011; Goggin et al, 2010; Pignocchi and Foyer, 2003). Ascorbate is present in animals and plants as ascorbate (reduced form), monodehydroascorbate (a radical that is formed after the loss of one electron), and dehydroascorbate (a somewhat more stable oxidized form that is created by the loss of two electrons).…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate has multiple functions in animals and plants, including acting as an antioxidant, serving as a cofactor for various enzymes, and participating in cell signalling (Corti et al, 2010; Foyer and Noctor, 2011; Goggin et al, 2010; Pignocchi and Foyer, 2003). Ascorbate is present in animals and plants as ascorbate (reduced form), monodehydroascorbate (a radical that is formed after the loss of one electron), and dehydroascorbate (a somewhat more stable oxidized form that is created by the loss of two electrons).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results show significant promise for the development of plants with enhanced abiotic stress tolerance, elevated AsA content may affect the ability of plants to interact with insects and other herbivores (Goggin et al 2010). Fine regulation of these genes may allow the production of transgenic plants, with tolerances to a wide range of stresses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the components of the plant antioxidant system is ascorbic acid (AsA) (Hancock & Viola, 2005). Several lines of research have previously suggested that AsA plays a key role in plant-insect interactions, as its abundance in plants modifies insect infestation ability and/or plant susceptibility to insect feeding (Goggin et al, 2010). Several mechanisms have been suggested by which AsA modulates insect success on plants: effects may be mediated by AsA as an essential dietary nutrient, as an antioxidant in the insect midgut neutralizing harmful H 2 O 2 , or as a substrate for plant-derived AsA oxidase, which can lead to generation of toxic ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of research have previously suggested that AsA plays a key role in plant-insect interactions, as its abundance in plants modifies insect infestation ability and/or plant susceptibility to insect feeding (Goggin et al, 2010). Ascorbic acid can also influence the efficacy of plant defences such as myrosinases and tannins, and alter insects' susceptibility to natural enemies (Goggin et al, 2010). Ascorbic acid can also influence the efficacy of plant defences such as myrosinases and tannins, and alter insects' susceptibility to natural enemies (Goggin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation